IMPROVING LITERACY AND NUMERATION ABILITY THROUGH A CAMPUS TEACHING PROGRAM AT SD NEGERI 091640 BANDAR MASILAM, SIMALUNGUN DISTRICT - Ance Siallagan; Diki Setiawan; Dina Valentina Pratiwi; Via Nirvana Sipayung; Rutiah Destriana Sitinjak; Putri Rahayu; Mustika Hati Purba (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
The Teaching Campus program is a form of Freedom to Learn Campus Merdeka, which provides opportunities for students to become partners of elementary and secondary school teachers who have been affected by the Covid-19 pandemic. Public Elementary School 091640 Bandar Masilam Simalungun Regency is one of the targeted schools for the campus teaching program batch 3 of 2022 due to experiencing learning loss during the pandemic. Students who experience learning loss have low literacy and numeracy skills, some are even unable to read at all. The method used is descriptive qualitative. The teaching campus program at SDN 091640 Bandar Masilam consists of activities to improve literacy and numeracy, teacher and school administration, technology adaptation, character development according to Pancasila values, and environmental health education. With the teaching campus program from February to June 2022, there has been an increase in students' literacy skills, numeracy skills. The existence of a reading corner makes students who have not been able to write and read at all be able to write and read fluently. The results of the class minimum competency assessment (AKM) were also very satisfying. In addition, school administration is getting more organized, implementing various online learning media applications, using electronic media in learning, as well as a clean and healthy school environment as a follow-up to school environmental health education. The Teaching Campus has provided space for students to contribute as agents of change/innovators so that it has a positive impact on all elements involved in the school environment.